« You don’t suspect me of doing anything wrong, do you ? » Peurs, soupçons et paranoïa dans The Woman in White de Wilkie Collins - Laurence Taleirach-Vielmas (Cahiers Victoriens et Edouardiens)
When Wilkie Collins launched the « sensation novel » with the publication of The Woman in White in 1859, he reworked late eighteenth-century gothic motifs and plot-patterns, and adapted them to the mid-Victorian modern world. In The Woman in White, mysterious, secretive and dangerous characters abound, from the ghostly virgin dressed in white who wanders at night and threatens to reveal secrets, to the Italian count and the British baronet who incarcerate the heroine under her half-sister’s name in a lunatic asylum in order to inherit her fortune. However, behind the domestic plot, anxieties related to foreigners and to the fears of foreign invasion seep through. The discovery of Sir Percival Glyde’s real identity or the recovery of Laura Fairlie’s identity fade behind the mysteries revolving around Collins’s modern villain, Count Fosco and many other Italian spies who endanger the British nation. This paper examines the fears and anxieties on which Collins’s novel hinges. From mere domestic secrets to anxieties related to national security, Collins describes a modern world ruled by suspicions, and constructs his characters as paranoid patients.